2008
DOI: 10.1007/s12272-001-2137-7
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of antibiotic rifampicin in poly(3-hydroxybutyrate-co-3-hydroxyvalerate)

Abstract: The aim of this study was the preparation of microparticles containing rifampicin using a biodegradable polymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) for oral administration produced by a bacteria. The poly(3-hydroxybutyrate-co-3-hydroxyvalerate) microparticles with and without rifampicin were prepared by the emulsification and solvent evaporation method, in which chloroform and polyvinyl alcohol are used as the solvent and emulsifier, respectively. Microparticles were obtained within a size range of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…26,27 Bacterial PHAs are typically produced with high molecular weight (M w ; i.e., 10 5 210 6 g/mol) and low polydispersity index. [33][34][35][36][37] Coimbra et al 33 prepared polymeric microspheres from biodegradable P(HB-6HV) copolymers and showed controlled release of a non-steroidal anti-inflammatory drug, flurbiprofen. 28 In addition, they can be produced with different side chain compositions, which alter their physical properties and render them useful for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Bacterial PHAs are typically produced with high molecular weight (M w ; i.e., 10 5 210 6 g/mol) and low polydispersity index. [33][34][35][36][37] Coimbra et al 33 prepared polymeric microspheres from biodegradable P(HB-6HV) copolymers and showed controlled release of a non-steroidal anti-inflammatory drug, flurbiprofen. 28 In addition, they can be produced with different side chain compositions, which alter their physical properties and render them useful for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] In order to improve the bioavailability of RIF and the other tuberculostatic drugs, several research groups have been developing drug delivery systems (DDS). [12] Suggested formulations involve hydrosoluble polymers, [15][16][17][18][19] solid dispersions, [20] microparticles, [9] liposomes, [21,22] inclusion complexes [23,24] and dendrimers [25]. Ideally, a DDS would transport the active compounds to their targets, reducing the therapeutic dosage while keeping the desired drug level for a long period of time, minimizing adverse effects and simplifying the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…PHA microparticles, films, and 3D matrices are promising carriers for antibiotics, enabling the sustained release of the drug [13][14][15][16]. Incorporation of protein compounds in composite microparticles consisting of PHAs and polyethylene glycol and polylactides was reported by Lionzo et al [9].…”
Section: Introductionmentioning
confidence: 99%